VD_FINDINFO HC / 2010 / 44 vom 3. Dezember 2009 - VD Tribunal cantonal (2009)
CONCOURS D'INFRACTIONS, AMENDE, FIXATION DE L'AMENDE, PRÉSOMPTION D'INNOCENCE | 106 CP, 47 CP, 49 ch. 1 CP, 411 let. g CPP, 411 let. i CPP, 415 CPP